Bending resistance of metal-concrete composite beams in a natural fire = Nośność na zginanie belek zespolonych metalowo-betonowych w pożarze naturalnym - Chybiński, Marcin; Polus, Łukasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this paper, the bending resistance of three metal-concrete composite beams was compared in real car fires in an open car park. Steel and concrete composite beams are often used for the construction of ceilings in multi-storey car parks. The authors made an attempt to evaluate how the replacement of a non-alloy steel girder with a stainless steel or aluminium alloy girder affects the bending resistance of a composite beam under fire conditions. The analysed beams were not fire-protected. They consisted of a concrete slab and a girder made of: non-alloy (carbon) S235J2 (1.0117) steel, X6CrNiMoTi17-12-2 (1.4571) stainless steel, and AW-6061 T6 (EN AW-Al Mg1SiCu) aluminium alloy.
Keywords: composite beams; fire; steel; stainless steel; aluminium alloy; open car park; belka zespolona; pożar; stal; stal nierdzewna; stop aluminium; garaż otwarty